Linear active disturbance rejection control of heavy-haul train operation based on an interval type-2 fuzzy logic system model. Issue 4 (31st December 2022) - Fu, Yating; Rao, Wenxuan; Yang, Hui
Abstract: The heavy-haul train (HHT) has large capacity and high efficiency, which represents the level of freight and makes the amelioration of control performance a trend in various countries. Improving the model reliability and increasing the anti-disturbance ability of the operation controller are two main ways to improve the operation control accuracy of HHTs. Herein, to describe the large nonlinear system more precisely, an interval type-2 fuzzy logic system (IT2FLS) is introduced to obtain a dynamic model. Then, a linear active disturbance rejection controller (LADRC) is designed to achieve precise operational control. In addition, the 'bandwidth method' is combined with the sparrow search algorithm (SSA) to solve the difficulty of controller parameters adjustment. Afterwards, the stability analysis of the closed-loop control system is given. The simulation experiments are conducted based on data collected from HXD1 locomotives driven by excellent drivers. Results show that the speed tracking error is no more than 0.5 km/h, and demonstrate that the proposed method significantly improves the operational performance of HHTs.